Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s11661-015-2851-2
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Ferrite Growth Kinetics under Denitriding and Decarburizing Conditions

Abstract: Recent years have seen an increasing emphasis on the identification of transitions in growth modes during the diffusional decomposition of austenite to ferrite in Fe-C-X alloys. Of particular interest are transitions between the extremes of non-partitioned growth represented by the ParaEquilibrium (PE) and local equilibrium negligible partition limits. Identification of such transitions requires high-quality measurements of ferrite growth kinetics, and recent uses of the decarburization approach have allowed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…It is well known that FIB milling can cause damage to the near-surface regions of a sample, resulting in atom displacements, vacancy generation, and the implantation of Ga ions (Giannuzzi & Stevie, 2005; Volkert & Minor, 2007). These effects may provide N atoms with sufficient energy to be ejected from the sample.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that FIB milling can cause damage to the near-surface regions of a sample, resulting in atom displacements, vacancy generation, and the implantation of Ga ions (Giannuzzi & Stevie, 2005; Volkert & Minor, 2007). These effects may provide N atoms with sufficient energy to be ejected from the sample.…”
Section: Resultsmentioning
confidence: 99%
“…This concentration decays rapidly with depth, until ~15–20 nm, after which the Ga content is only present at background levels. Assuming the FIB milling to be operating in the linear cascade regime (Giannuzzi & Stevie, 2005), there is the possibility that the collision cascades caused by the incident Ga ions affect N at greater depths than those reached by the Ga ions themselves; however, in a relatively dense material such as steel, the depth of the collision cascade should not be far greater than the Ga ion penetration depth. An approximation of the collision depth in the Fe–Mn–N martensite samples is made by modeling with the stopping and range of ions in matter (SRIM) software package (Ziegler, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ternary Fe-N-Mn alloys were then produced using controlled nitriding of the Fe-0.5Mn binary. The full details for these processes are given by Guo et al [14]. The exact composition of the alloys used in this study are shown in Table 1.…”
Section: Decarburization and Nitriding Experimentsmentioning
confidence: 99%
“…In another approach, the effects can be studied by conducting austenite to ferrite phase transformation experiments in series of Fe-C-Mn and Fe-N-Mn ternary steels. In this regard, a series of recent experimental studies on ferrite growth during controlled decarburizing and denitriding [14,15], have suggested interfacial segregation of Mn in presence of C, but no sign of interfacial segregation of Mn in Fe-N-Mn. These findings, based on analysis of the growth kinetic data, is consistent with the preceding accepted perception [8,16e18] that the presence of interstitial elements influences the tendency of the substitutional alloying element to segregate to the interface.…”
Section: Introductionmentioning
confidence: 98%